VIGS as a strategy to reverse aphid wing induction by Y‐satellite RNA of cucumber mosaic virus - Hangil Kim; Chikara Masuta (FEBS Open Bio, 2023)
Y‐satellite RNA (Y‐sat) of cucumber mosaic virus upregulates the expression of the aphid ABCG4 gene, which promotes aphid wing formation. We used ABCG4 virus‐induced gene silencing (VIGS) to prevent the wing‐induction mechanism of Y‐sat and thus inhibited aphid wing formation. Of the aphids on plants with VIGS of ABCG4, only about 30% had wings, and 60–70% of the winged aphids were small and likely impaired in flying ability. In addition, we showed that double‐stranded RNAs (dsRNAs) and small RNAs were transferred from the plant to the aphid to adequately silence aphid genes. Supplying ABCG4 dsRNA by VIGS to aphids is thus a potential strategy to inhibit aphid wing formation.